2017
DOI: 10.1016/j.quascirev.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the last two glacial maxima and implications for ice-sheet, δ18O, and sea-level reconstructions

Abstract: Arctic ice shelf Last Interglacial Glacioisostatic adjustment a b s t r a c t Studies of past glacial cycles yield critical information about climate and sea-level (ice-volume) variability, including the sensitivity of climate to radiative change, and impacts of crustal rebound on sealevel reconstructions for past interglacials. Here we identify significant differences between the last and penultimate glacial maxima (LGM and PGM) in terms of global volume and distribution of land ice, despite similar temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 350 publications
(383 reference statements)
2
120
0
2
Order By: Relevance
“…To what extent the global ice volume indicators reflect the spatial extent of individual continental ice sheets across these two glacial periods, however, is still uncertain. Prior studies found that European ice sheets were larger during MIS 6 than MIS 2 (Rohling et al, ), and in North America, ice extent during the Illinoian glacial phase has been reconstructed to be as or more extensive than the Wisconsin glaciation in the upper Midwest (Curry et al, ; Syverson & Colgan, ). How the local LIS spatial extent correlates with permafrost conditions in North America is also not well understood for all glaciations.…”
Section: Paleo‐permafrost Conditions Across the Last Two Glacial Perimentioning
confidence: 99%
“…To what extent the global ice volume indicators reflect the spatial extent of individual continental ice sheets across these two glacial periods, however, is still uncertain. Prior studies found that European ice sheets were larger during MIS 6 than MIS 2 (Rohling et al, ), and in North America, ice extent during the Illinoian glacial phase has been reconstructed to be as or more extensive than the Wisconsin glaciation in the upper Midwest (Curry et al, ; Syverson & Colgan, ). How the local LIS spatial extent correlates with permafrost conditions in North America is also not well understood for all glaciations.…”
Section: Paleo‐permafrost Conditions Across the Last Two Glacial Perimentioning
confidence: 99%
“…The LIG is characterised by higher GMSL than present day (+6.6 to +11.4 m) (Grant et al, 2014;Dutton et al, 2015;Turney and Jones, 2010;Buizert et al, 2014;Rohling et al, 2017). Here we quantified the contribution of the relatively high temperatures on global sea levels through ocean thermal expansion (Table 2).…”
Section: Thermal Expansion Contribution To Last Interglacial Sea Levelmentioning
confidence: 99%
“…Described as a 'super-interglacial' (Turney and Jones, 2010;Overpeck et al, 2005), the LIG was one of the warmest periods of the last 800 kyr, experiencing relatively higher polar temperatures compared to the global mean ('polar amplification') (Past Interglacials Working Group of PAGES, 2016;Hoffman et al, 2017;Turney and Jones, 2010;Capron et al, 2017), with the most geographically widespread expression of high Global Mean Sea Level in the recent geological record (GMSL, +6.6 to +11.4 m) (Dutton et al, 2015;Grant et al, 2014;Kopp et al, 2009;Rohling et al, 2017), abrupt shifts in regional hydroclimate (Thomas et al, 2015), and elevated atmospheric CO2 concentrations (relative to the pre-industrial period) of ~290 ppm (Buizert et al, 2014;Köhler et al, 2017), suggesting non-linear responses in the Earth system to forcing (Thomas, 2016).…”
mentioning
confidence: 99%
“…Samples from an eastern Mediterranean Sea core (MS21PC; 32°20.7'N, 31°39.0'E; 1022 m water depth) (Hennekam et al, 2015;Rohling et al, 2017;Zwiep et al, in press) were used to determine and test the optimal settings for trace metal analyses. Total core length is 751.5 cm, but this study focuses only on the top 1.5 meters and bottom 2 meters of the core, containing sapropel layers S1…”
Section: Mediterranean Sediment Materials To Test Optimal Trace Metal mentioning
confidence: 99%